Effect of the Coronavirus Disease 2019 Pandemic on School-going Children - Khare, Sumit (International Journal of Nursing Research, 2023)
Coronavirus disease 2019 (COVID-19) pandemic and lockdown have brought about a sense of fear and anxiety around the globe. Having the second largest population along with poor health infrastructural facilities, India has fairly performed well in its initial fight against COVID-19 as compared to the far developed and equipped countries. COVID-19 led to short term as well as long-term psychosocial and mental health implications for children and adolescents. The quality and magnitude of impact on minors are determined by many vulnerability factors such as developmental age, educational status, pre-existing mental health condition, being economically underprivileged or being quarantined due to infection or fear of infection. Anxiety, depression, irritability, boredom, inattention, and fear of COVID-19 are predominant new-onset psychological problems in children during the COVID-19 pandemic. Children with pre-existing behavioral problems such as autism and attention deficit hyperactivity disorder have a high probability of worsening of their behavioral symptoms. There is a pressing need for longitudinal and developmental studies, and implementing evidence based elaborative plan of action to cater to the psycho-social and mental health needs of the vulnerable children and adolescents during pandemic as well as post pandemic. Furthermore, to ameliorate children and adolescents access to mental health support services geared towards providing measures for developing healthy coping mechanisms during the current crisis. For this innovative child and adolescent mental health policies with direct and digital collaborative networks of psychiatrists, psychologists, pediatricians, and community volunteers are deemed necessary.